Reducing Your Risk for Diabetes: A Resource Guide - Linda B. Bobroff (EDIS)
FCS-8840, a 2-page annotated bibliography by Linda B. Bobroff, lists some of the many resources that are available to help people of all backgrounds lead healthier lives and reduce their risk for diabetes. Published by the UF Department of Family, Youth, and Community Sciences, May 2007.